Investigation of sarcopenia in hemodialysis patients in Adiyaman province - Gürbüzcan, Aysun; Cakmak, Erkan; Bilen, Nurhan; Akel, Mustafa; Gurel, Ali; Selçuk, Mustafa Yavuz (My University, 2021)
In this study, we aimed to evaluate the presence and frequency of sarcopenia in chronic kidney disease (CKD) patients under hemodialysis treatment, to analyze socio-de- mographic and clinical factors that may be associated with sarcopenia and to compare them with the control group. This study includes a sample of 61 patients over the age of 18, affected by stage 4 CKD under hemodialysis treatment at least six months, being followed in our CKD outpatient clinic and 55 healthy controls. In all patients, demographic characteristics such as gender and age, anthropometric characteristics such as height, weight, body mass index (BMI), waist circumference, upper arm circumference, hip circumference, calf circumference and skin thickness were measured. Body compositions was determined using a Bioelectrical Impedance Analyzer (BIA). In the evaluation of sarcopenia, hand grip strength with hand dynamometer, walking speed with 6 meter walking test and muscle mass with BIA were analyzed. European Working Group on Sarcopenia in Older People (EWGSOP) criteria were preferred for the diagnosis of sarcopenia. The prevalence of sarcopenia was 5.5% in the control group and 31.1% in the hemodialysis group. The incidence of sarcopenia was significantly higher in patients under hemodialysis treatment than controls. Sarcopenia is common in patients with CKD under hemodialysis treatment. In this patients, sarcopenia was associated with anthropometric measurements such as BMI, waist circumference, arm circumference, hip circumference, calf circumference, skin thickness.
Keywords: Hemodialysis; Sarcopenia; anthropometric